2007
DOI: 10.1093/schbul/sbm008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toxoplasma gondii Infection on the Brain

Abstract: Toxoplasma gondii, an intracellular protozoan parasite, can infect humans in 3 different ways: ingestion of tissue cysts, ingestion of oocysts, or congenital infection with tachyzoites. After proliferation of tachyzoites in various organs during the acute stage, the parasite forms cysts preferentially in the brain and establishes a chronic infection, which is a balance between host immunity and the parasite's evasion of the immune response. A variety of brain cells, including astrocytes and neurons, can be inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
196
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(205 citation statements)
references
References 76 publications
1
196
0
8
Order By: Relevance
“…[1][2][3] Toxoplasma gondii can infect humans in 3 different ways: ingestion of tissue cysts, ingestion of oocysts, or congenital infection with tachyzoites. 4 Within a short period of time the tachyzoite form of the parasite actively crosses the gastrointestinal barrier by penetrating enterocytic cells in the small intestine and entering submucosal tissue. 5,6 Intracellular tachyzoites form a parasitophorous vacuole that ruptures following multiple cycles of replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Toxoplasma gondii can infect humans in 3 different ways: ingestion of tissue cysts, ingestion of oocysts, or congenital infection with tachyzoites. 4 Within a short period of time the tachyzoite form of the parasite actively crosses the gastrointestinal barrier by penetrating enterocytic cells in the small intestine and entering submucosal tissue. 5,6 Intracellular tachyzoites form a parasitophorous vacuole that ruptures following multiple cycles of replication.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Latent infection with T. gondii involves an elaborate interplay between the parasite and the host in which the parasite ensures its survival and proliferation but avoids fatal damage to the host at the same time. 10 By definition, latent infections involve a complex interplay between parasite and host, producing some degree of harmony. In humans, T. gondii performs a delicate balancing act that involves, on the one hand, modification of its proximal (and perhaps distal) environment in ways to promote its survival and transmission and, on the other hand, avoidance of overt tissue damage (directly from the parasite or indirectly from the immune response) that would lead to the demise of its host.…”
Section: Discussionmentioning
confidence: 99%
“…gondii, which can lead to abnormalities in these regions [4]. Another hypothesis that could explain the biological plausibility is the interference of T. gondii with neurotransmitter function.…”
Section: Psychosismentioning
confidence: 99%
“…Studies of animal brain biopsies have shown T. gondii to have high neurotropism, with the capacity to infect glial cells (especially microglia and astrocytes) and neurons, forming persistent cysts in brain tissue [69]. Although no tropism for specific brain regions has been observed, with cysts being detected in many areas, the most frequently parasitized regions are the hippocampus, thalamus, cerebral cortex, cerebellum, olfactory bulb, and, especially, the amygdala [70][71][72][73].…”
Section: Studies Based On Toxoplasma Gondii Nucleic Acid Detectionmentioning
confidence: 99%